CaLa2FeCoSbO9 and ALa2FeNiSbO9 (A = Ca, Sr, Ba): cation-ordered, inhomogeneous, ferrimagnetic perovskites - Hendrickx, M; Tang, Y; Hunter, EC; Battle, PD; Cadogan, JM; Hadermann, J (Elsevier, 2020)
Polycrystalline samples of CaLa2FeCoSbO9 and ALa2FeNiSbO9 (A ​= ​Ca, Sr, Ba) have been prepared in solid-state reactions and studied by a combination of transmission electron microscopy, magnetometry, X-ray diffraction, neutron diffraction and Mössbauer spectroscopy. Diffraction and TEM showed that each shows 1:1 ​B-site ordering in which Co2+/Ni2+ and Sb5+ tend to occupy two distinct crystallographic sites while Fe3+ is distributed over both sites. While X-ray and neutron diffraction agreed that all four compositions are monophasic with space group P21/n, TEM revealed different levels of compositional inhomogeneity at the subcrystal scale, which, in the case of BaLa2FeNiSbO9, leads to the occurrence of both a P21/n and an I2/m phase. Magnetometry and neutron diffraction show that these perovskites are ferrimagnets with a G-type magnetic structure. Their relatively low magnetisation can be attributed to their inhomogeneity. This work demonstrates the importance of studying the microstructure of complex compositions.